Changes of equality of medical service utilization in China between 1993 and 2018: findings from six waves of nationwide household interview survey - Ming Wu; Ju Huang; Hongqiao Fu; Xueqin Xie; Shiyong Wu (BMC, 2023)
Abstract Background Changes in China's health care system in the last three decades was remarkable. The current study aims on examine the change of equality of health care utilization in mainland China based on a nationwide household interview survey. Methods We used household interview data extracted from six waves of National Health Service Survey between 1993 and 2018. Changes of health care utilization were descripted. Equality of the utilization were examined with univariate meta-regression across urban and rural areas, socioeconomic development regions and income groups. Results The proportion of outpatient visits within last two weeks experienced a decrease from 17.0% in 1993 to 13.0% in 2013 and bounced back to 24.0% in 2018. The age-standardized trend remained unchanged. Hospitalization in the last 12 month increased from 2.6% in 1998 to 13.8% in 2018. The perceived unmet need of hospital admission fell from 35.9% in 1998 to 21.5% in 2018. The gaps in health care utilization between urban and rural areas, across regions and by income groups have been narrowed, implying improved equality of using medical services in the last two and a half decades. Conclusion China has experienced significant increases in health care utilization over the past 25 years. Meanwhile, the unmet needs for health care decreased remarkably and the equality of health care utilization improved significantly. These results imply significant achievements in health service accessibility in China.